THE EFFECT OF PROMOTION ON THE INTERESTS OF SALIC PAYING ZAKAT, INFAQ AND SHADAQAH IN AMIL ZAKAT INFAQ AND SHADAQAH JAGAD 'ALIMUSSIRRY INSTITUTIONS - Arilia, Linawati (Journal Intellectual Sufism Research (JISR), 2020)
Indonesia is the fourth most populous country in the world with a population of 265 million. there are 17 LAZ at national level, 7 LAZ at provincial level and 11 LAZ at district level, the data is LAZ registered at baznas.go.id. The national zakat potential reaches Rp 217 trillion expected to be able to overcome the problem of poverty found in Indonesia . promotion factors become the most important means to attract and retain members. One of the promotional objectives of the amil zakat institution is to inform all types of products offered and try to attract new members. This study is a quasi-experimental study, researchers do not have the flexibility to manipulate subjects. The research design used in this study was "One Groups Pretest-Posttest Design". The effect of promotion on the interest in salik to pay zakat in the Amil zakat institution Aladussirry before being given treatment in the form of brochures is still low or not significantly. The effect of promotion on the interest of salik to pay zakat in the Amil zakat organization Jagad 'Alimussirry after being given treatment in the form of brochures was very high or significantly.